Reconciling mantle attenuation‐temperature relationships from seismology, petrology, and laboratory measurements. (4th September 2014) - Abers, G. A.; Fischer, K. M.; Hirth, G.; Wiens, D. A.; Plank, T.; Holtzman, B. K.; McCarthy, C.; Gazel, E.
Abstract Seismic attenuation measurements provide a powerful tool for sampling mantle properties. Laboratory experiments provide calibrations at seismic frequencies and mantle temperatures for dry melt‐free rocks, but require ∼102−103 extrapolations in grain size to mantle conditions; also, the effects of water and melt are not well understood. At the same time, body wave attenuation measured from dense broadband arrays provides reliable estimates of shear wave attenuation ( <alternatives><inline-graphic mimetype="image" xlink:href="ark:/27927/pgh3m44wg2h" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />QS−1</alternatives>), affording an opportunity for calibration. We reanalyze seismic data sets that sample arc and back‐arc mantle in Central America, the Marianas, and the Lau Basin, confirming very high attenuation (QS ∼ 25–80) at 1 Hz and depths of 50–100 km. At each of these sites, independent petrological studies constrain the temperature and water content where basaltic magmas last equilibrated with the mantle, 1300–1450°C. The QS measurements correlate inversely with the petrologically inferred temperatures, as expected. However, dry attenuation models predict QS too high by a factor of 1.5–5. Modifying models to include effects of H2O and rheology‐dependent grain size shows that the effects of water‐enhanced dissipation and water‐enhanced grain growth nearly cancel, so H2O effects are modest. Therefore, high H2O in the arc source region cannot explain the low QS, nor in the back arc where lavas show modest water content. Most likely, the high attenuation reflects the presence of melt, and some models of melt effects come close to reproducing observations. Overall, body wave QS can be reconciled with petrologic and laboratory inferences of mantle conditions if melt has a strong influence beneath arcs and back arcs.